Mutational phospho-mimicry reveals a regulatory role for the XRCC4 and XLF C-terminal tails in modulating DNA bridging during classical non-homologous end joining - Normanno, Davide; Négrel, Aurélie; de Melo, Abinadabe J; Betzi, Stéphane; Meek, Katheryn; Modesti, Mauro (eLife, 2017)
XRCC4 and DNA Ligase 4 (LIG4) form a tight complex that provides DNA ligase activity for classical non-homologous end joining (the predominant DNA double-strand break repair pathway in higher eukaryotes) and is stimulated by XLF. Independently of LIG4, XLF also associates with XRCC4 to form filaments that bridge DNA. These XRCC4/XLF complexes rapidly load and connect broken DNA, thereby stimulating intermolecular ligation. XRCC4 and XLF both include disordered C-terminal tails that are functionally dispensable in isolation but are phosphorylated in response to DNA damage by DNA-PK and/or ATM. Here we concomitantly modify the tails of XRCC4 and XLF by substituting fourteen previously identified phosphorylation sites with either alanine or aspartate residues. These phospho-blocking and -mimicking mutations impact both the stability and DNA bridging capacity of XRCC4/XLF complexes, but without affecting their ability to stimulate LIG4 activity. Implicit in this finding is that phosphorylation may regulate DNA bridging by XRCC4/XLF filaments. DNA in human and other animal cells is organised into structures called chromosomes. One of the most dangerous types of DNA damage is a double-strand break, where both strands of the DNA helix are broken in the same place. If this damage is not repaired it can be serious enough to kill the cell. If the DNA is repaired badly, part of one chromosome can become attached to another – a defect known as a chromosome translocation. Fortunately, cells are equipped with machineries that can recognise and fix these breaks. One of these processes is known as “non-homologous end joining” and it involves a set of proteins including two known as XRCC4 and XLF. These proteins work like a bandage, holding together the broken DNA until it is repaired. Both proteins have long tails, but the role of these structures was not clear. During DNA repair, the cell chemically modifies the tails of these proteins by a process called phosphorylation. However, previous studies have found that it is possible to prevent the modification of the tail of one of the proteins, or even remove the tail entirely, without affecting the repair process. Here, Normanno et al. investigated the effect of blocking the modification of the tails of both proteins at the same time. For the experiments, the tails were both altered in various places to either block or mimic the phosphorylation that normally occurs during DNA repair. Mimicking the phosphorylation of both tails affected the ability of XRCC4 and XLF to stay attached to the DNA, suggesting that the phosphorylation helps these proteins to detach from the DNA once the repair is complete. Furthermore, in human embryonic kidney cells the altered proteins were less able to repair DNA damage in response to a drug that causes double-strand breaks. These findings improve our understanding of how cells repair their DNA to maintain a complete set of genetic information. Defects in DNA repair are linked to conditions where the brain does not develop properly, whilst some cancer therapies deliberately inflict double-strand breaks to kill cancer cells. In the future, these findings may lead to improvements in radiotherapy and other treatments for human diseases.